2019
DOI: 10.1101/798975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MARSHAL, a novel tool for virtual phenotyping of maize root system hydraulic architectures

Abstract: Functional-structural root system models combine functional and structural root traits to represent the growth and development of root systems. In general, they are characterized by a large number of growth, architectural and functional root parameters, generating contrasted root systems evolving in a highly nonlinear environment (soil, atmosphere), which makes unclear what impact of each single root system on root system functioning actually is. On the other end of the root system modelling continuum, macrosc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In the future, more extended coupling could make use of CRootbox' ability to compute not only the RLD in each soil layer but also root water uptake sink terms for each soil layer based on root hydraulic architecture.The common variable of both models would be root water uptake per layer, and CRootbox would not only pass the RLD but also the root water uptake to SIMPLACE and get the soil matrix potential in each layer from the SIMPLACE soil component beforehand. This will enable to include further processes not accounted for in the current simulations, i.e., root water uptake compensation and recognition of local root hydraulic properties (Meunier et al, 2019 ). Further field data (more seasons per cultivar, more sites) would allow for more robust model calibration.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, more extended coupling could make use of CRootbox' ability to compute not only the RLD in each soil layer but also root water uptake sink terms for each soil layer based on root hydraulic architecture.The common variable of both models would be root water uptake per layer, and CRootbox would not only pass the RLD but also the root water uptake to SIMPLACE and get the soil matrix potential in each layer from the SIMPLACE soil component beforehand. This will enable to include further processes not accounted for in the current simulations, i.e., root water uptake compensation and recognition of local root hydraulic properties (Meunier et al, 2019 ). Further field data (more seasons per cultivar, more sites) would allow for more robust model calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Meunier et al (2020) showed that modifying hydraulic properties changes the root system hydraulic architecture and thus affects the whole root system conductance ( K rs ). Tuning root hydraulic conductivity functions to match experimental data or test new hypotheses through simulation studies could therefore show the local impact of root anatomy or cell hydraulic properties on the whole root system conductance.…”
Section: Discussionmentioning
confidence: 99%
“…We posit our approach will allow more realistic parametrizations of functional–structural plant models targeting root water uptake. Such a root hydraulic conductivity atlas can as well be connected to complementary modeling tools (e.g., Meunier et al, 2020) to estimate hydraulic parameters such as the root system conductance or the standard sink fraction for models working at larger scales (e.g., Agee et al, 2021; Cai et al, 2018; Sulis et al, 2019), as envisioned by Passot et al (2019). Future modeling studies could reuse the anatomical networks and the root hydraulic conductivities that we built on their root system architecture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations